Optimalisasi Platform Digital sebagai Media Dakwah dan Ekonomi: Strategi Peningkatan Pendapatan UMKM di Indonesia - Nabila, Putri; Nisrina, Risa; Habibie, Muhammad Rizky; Ali, Yusuf (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Digital transformation has become a key catalyst in enhancing the competitiveness and sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Alongside technological advancement, digital platforms serve not only as tools for increasing revenue but also as effective media for Islamic da'wah by embedding religious values within business practices. This study aims to analyze digital platform optimization strategies that support MSME economic growth while exploring the integration of Islamic da'wah values within the context of business digitalization. A qualitative approach was employed using a systematic literature review of 45 academic publications and official reports published between 2020 and 2024. The findings indicate that 88.37% of MSMEs that adopted digital platforms experienced increased revenue, with 66.28% reporting gains of up to 50%. The most widely used platforms include Shopee (50%), Facebook Marketplace (33.46%), and Instagram Shop (28.74%). Identified optimization strategies include dynamic pricing, personalized services driven by artificial intelligence, integration of digital payment systems, and the use of data analytics. Additionally, embedding da'wah content—such as product narratives emphasizing honesty, blessings (barakah), and social responsibility—contributes to building an ethical and trustworthy business image. Key challenges include low levels of digital literacy, infrastructure disparities, and limited promotional resources. This study contributes theoretically by formulating a conceptual framework for platform optimization rooted in Islamic values and offers practical recommendations for MSME actors and policymakers to develop a competitive and ethical digital ecosystem.